Hyperlipidemia and Long-Term Outcomes in Nondiabetic Chronic Kidney Disease - Chawla, Varun (American Society of Nephrology, 2010)
Background and objectives: Dyslipidemia confers a paradoxical survival advantage in patients with kidney failure. Data are limited in the earlier stages of chronic kidney disease (CKD). Design, setting, participants, and measurements: This was a cohort study in 840 subjects with stage 3 to 4 CKD enrolled in the Modification of Diet in Renal Disease study. Cox models were used to examine the relationship of total cholesterol (TC), non-HDL-cholesterol (NHDL-C), triglycerides (TG), and HDL-cholesterol (HDL-C) with all-cause and cardiovascular disease (CVD) mortality and progression to kidney failure. Results: During a mean follow-up of 10 years, there were 208 deaths, 128 deaths from CVD, and 554 subjects reached kidney failure. There was no association between tertiles of any of the lipid variables and mortality; the lowest HDL-C tertile (1.44, 1.18 to 1.78) had increased risk of kidney failure but covariate adjustment abolished this association. In analyses with lipids as continuous variables, there was a significant association with all-cause mortality for TC (hazard ratio [HR] per 10-mg/dl increase, 95% confidence intervals [CI] = 1.03, 1.0 to 1.06) that disappeared with covariate adjustment; there was no association of TG, HDL-C, and NHDL-C as continuous variables with all-cause or CVD mortality. There was a significant inverse association between HDL-C and kidney failure (HR = 0.93, CI = 0.87 to 0.99) in an unadjusted Cox model that was attenuated after adjustment for covariates (HR = 0.98 CI = 0.91 to 1.06). Conclusions: In this cohort, with predominantly nondiabetic CKD patients, hyperlipidemia is not an independent predictor of long-term outcomes.